How Young Learners Learn English: Developmental Differences in Experience, Interaction, and Engagement - Inda Indrawati; Andi Mohammad Abrar; Diyenti Rusdin; Hidayati; Sri Sudaryati; Marzuki (Sakura Digital Nusantara, 2026)
Purpose: This study examined observable patterns of English learning in two primary school classrooms by investigating learners' cognitive behaviours, classroom involvement, interactions, and task responses across two grade levels. Methods: A qualitative multiple-case study was conducted in two Indonesian public elementary schools involving 50 learners (27 Grade 1 and 23 Grade 4 students). Data were collected through structured non-participant classroom observations supported by video recordings and field notes. The data were analysed in two stages. First, each classroom was analysed independently to identify patterns of learners' observable cognitive behaviours, classroom involvement, interactions, and task responses. Second, a cross-case thematic analysis was conducted to identify recurring patterns of observable English learning across the two classrooms. Findings: The classroom observations identified differences in learners' cognitive behaviours and classroom involvement across the two grade-level classrooms. In the observed Grade 1 classroom, learners relied more frequently on teacher modelling, concrete experiences, repetition, and structured guidance, whereas learners in the Grade 4 classroom more often drew on prior knowledge, collaborated with peers, and responded to classroom tasks with greater independence. Across both classrooms, three recurring patterns of observable English learning activities were identified: learning through experience, learning through interaction, and learning through engagement. Research Implications: The findings suggest that instructional practices responsive to learners' observable cognitive behaviours, classroom involvement, and interaction patterns may better support English learning in primary school classrooms. Originality: This study contributes context-specific evidence on observable classroom behaviours associated with English learning, extending understanding of how learners participated in English lessons across two primary school classrooms.